If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5y-3y-13=27.64
We move all terms to the left:
5y-3y-13-(27.64)=0
We add all the numbers together, and all the variables
2y-40.64=0
We move all terms containing y to the left, all other terms to the right
2y=40.64
y=40.64/2
y=20+0.64/2
| -5x+15=3(11-x) | | -4.5x+1.7=5x+81.5 | | -4(7n-4)=-9(7n+6) | | X-(4x-2)=-10x+23 | | 96.3=9(m+3.8) | | 2x11=7 | | 12x+16x=64 | | 4()3x+1=-2(5x-2) | | 3a+a=1.60 | | 3a=1.60 | | a+a=1.60 | | a4=1.60 | | 6b+4=-2b-16 | | 79.8=7(m+3.6) | | 0=5x^2-7x+9 | | 4a=1.60 | | 10x+13=5x+76.5 | | 3x-13=4(x-4) | | 79.8=7(m+3.6 | | 2(-7x+2)=4 | | -6(2-x)+3(x-4)=12 | | 4y+7+y=10+3y | | s+s=18 | | -282=-6(5+7x) | | n=3•45 | | s/2=18 | | 1800-×=3x | | -4(2x+4)=104 | | 23=4×t-7-t | | 5x+5=80+5x | | -90=5(7x+10) | | 8x-2x+64=8x+30 |